Establishment and multiapproach characterization of Amblyomma sculptum (Acari: Ixodidae) cell line (ASE-14) from Brazil - Lima-Duarte, Leidiane; Castro-Santiago, Ana Carolina; Camargo, Jaqueline Valéria [UNESP]; Ferretti, Ana Beatriz Stein Machado [UNESP]; Anholeto, Luís Adriano [UNESP]; Pereira, Melissa Carolina [UNESP]; Ikeda, Priscila [UNESP]; Perez, Carlos Alberto; Sanches, Gustavo Seron; Camargo-Mathias, Maria Izabel [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Machado, Rosangela Zacarias [UNESP]; et al. (Elsevier, 2022)
The establishment and characterization of the ASE-14 cell line derived from embryos of Amblyomma sculptum is described here. Primary cultures were started, and after 60 days of culturing a confluent monolayer was formed and the first subculture was then carried out. After this, new subcultures were carried out every 4 weeks. Cryopreservation of cells was successful only after the 14th subculture. We compared the chromosomes of the ASE-14 cell line with those of parental ticks. Cytogenetic analysis revealed occurrences of variable and increased diploid numbers in the ASE-14 cell line in comparison with adult ticks, probably through polyploidization events, chromosome fusions and translocations, which allowed generation of cells with distinct diploid numbers. Confirmation of the origin of the A. sculptum cell line was obtained through conventional PCR and sequencing of a fragment of the mitochondrial 16S rRNA gene. In addition, no DNA from Anaplasma marginale, Anaplasma spp., Babesia/Theileria spp., Bartonella spp., Coxiella spp., Ehrlichia canis, Mycoplasma spp. or Rickettsia spp. was detected in the cells through PCR assays. Cytological analyses were performed using live phase contrast microscopy and cytocentrifuge smears stained with Giemsa, while periodic acid-Schiff and bromophenol blue staining techniques were used to detect polysaccharides and protein, respectively. In conclusion, a new cell line derived from embryos of A. sculptum was generated and characterized in this study. The ASE-14 cell line was deposited in the Tick Cell Biobank at the University of Liverpool, and in the Tick Cell Biobank South America Outpost at the Oswaldo Cruz Foundation (FIOCRUZ). The ASE-14 cell line is an important addition to the existing panel of tick cell lines and can be used as a tool for advancing research in various areas of the virology, bacteriology, biology and control of this tick.
Keywords: Brazil; chromosome; tick cell line